Impact of Systematic Whole-body 18F-Fluorodeoxyglucose PET/CT on the Management of Patients Suspected of Infective Endocarditis: The Prospective Multicenter TEPvENDO Study. (3rd June 2020) - Duval, Xavier; Le Moing, Vincent; Tubiana, Sarah; Esposito-Farèse, Marina; Ilic-Habensus, Emila; Leclercq, Florence; Bourdon, Aurélie; Goehringer, François; Selton-Suty, Christine; Chevalier, Elodie; Boutoille, David; Piriou, Nicolas; et al.
Abstract: Background: Diagnostic and patients' management modifications induced by whole-body 18 F-FDG-PET/CT had not been evaluated so far in prosthetic valve (PV) or native valve (NV) infective endocarditis (IE)-suspected patients. Methods: In sum, 140 consecutive patients in 8 tertiary care hospitals underwent 18 F-FDG-PET/CT. ESC-2015-modified Duke criteria and patients' management plan were established jointly by 2 experts before 18 F-FDG-PET/CT. The same experts reestablished Duke classification and patients' management plan immediately after qualitative interpretation of 18 F-FDG-PET/CT. A 6-month final Duke classification was established. Results: Among the 70 PV and 70 NV patients, 34 and 46 were classified as definite IE before 18 F-FDG-PET/CT. Abnormal perivalvular 18 F-FDG uptake was recorded in 67.2% PV and 24.3% NV patients respectively ( P < .001) and extracardiac uptake in 44.3% PV and 51.4% NV patients. IE classification was modified in 24.3% and 5.7% patients ( P = .005) (net reclassification index 20% and 4.3%). Patients' managements were modified in 21.4% PV and 31.4% NV patients ( P = .25). It was mainly due to perivalvular uptake in PV patients and to extra-cardiac uptake in NV patients and consisted in surgery plan modifications in 7 patients, antibiotic plan modifications in 22 patients and both in 5 patients. Altogether, 18 F-FDG-PET/CT modified classification and/or care in 40% of the patients (95% confidence interval: 32–48), which was most likely to occur in those with a noncontributing echocardiography ( P < .001) or IE classified as possible at baseline ( P = .04), while there was no difference between NV and PV. Conclusions: Systematic 18 F-FDG-PET/CT did significantly and appropriately impact diagnostic classification and/or IE management in PV and NV-IE suspected patients. Clinical Trials Registration: NCT02287792. Abstract : In 140 patients suspected of having prosthetic or native valve infective endocarditis, systematic whole body 18 F-FDG-PET/CT modified diagnosis classification in 15% of and/or care in 26% of them. Both prosthetic valve and native valve patients benefit from this systematic 18 F-FDG-PET/CT.